Flexible Approach In English Language Learning Curriculum Design: Optimizing Teaching In Merdeka Curriculum - Irsyad, Syifa Fauziah; Syarif, Hermawati; Zainil, Yetti (Eduvest - Journal of Universal Studies, 2024)
The Merdeka Curriculum implemented in Indonesia aims to create an education system that is more adaptive and responsive to local and global needs. In English language teaching, curriculum flexibility allows teachers to adjust learning materials to students' local contexts, thus encouraging student engagement in the learning process. This study aims to explore the application of flexibility in English curriculum design under the Merdeka Curriculum in five junior high schools in Solok City, West Sumatra. A qualitative approach with a case study method was used, with data collected through in-depth interviews, classroom observations, and student interviews. The results showed that flexibility in the preparation of teaching materials and teaching methods allowed teachers to adjust teaching to local needs. However, teachers faced challenges in balancing local materials with national competency standards and limited resources. This flexibility increased student engagement, although some students struggled without adequate guidance. In conclusion, support in the form of guidance, training, and additional resources are needed to optimize the implementation of curriculum flexibility